Vitamin K1 Inhibition of Renal Crystal Formation through Matrix Gla Protein in the Kidney - Yang Li; Xiuli Lu; Baoyu Yang; Jing Mao; Shan Jiang; Daojun Yu; Jichuan Pan; Tiange Cai; Takahiro Yasui; Bing Gao (Kidney & Blood Pressure Research, 2019)
Background and Objectives: Vitamin K (VK) plays a major role in modifying the binding of calcium in bones and blood vessels. Understanding the effect of VK on crystal formation in the kidney would contribute to advancing the treatment and prevention of kidney stones. Methods: Rats were treated with vitamin K1 (VK1) for 8 weeks. VK1 levels were detected and crystal formation were observed. HK2 cells were exposed to calcium oxalate monohydrate crystals. Apoptosis and cell viability were detected. Crystal deposition was analyzed using atomic absorption assay. The adenovirus vectors expressing matrix Gla protein (MGP) and siMGP were constructed to elucidate the effect and mechanism of VK1 on crystal formation. MGP expression in vivo and in vitro was analyzed by Western blot. The mRNA levels of monocyte chemoattractant protein-1 (MCP-1) and collagen I was measured by semiquantitative RT-PCR. Results: The concentrations of VK1 in whole blood and kidney tissues rose under treatment with VK1. Crystal formation was inhibited from the second to the 6th week, the frequency and quality of crystal formation decreased significantly, and the location of crystal formation was limited to a greater extent in the rats treated by VK1 compared to the control group. Warfarin treatment in the crystals-exposed HK2 cells significantly increased the number of crystals adhering to cells and the number of apoptotic cells and reduced cell viability. VK1 treatment reversed warfarin’s above influence. VK1 inhibited the upregulations of MCP-1 and collagen I in kidney tissues under crystal load. VK1 treatment increased MGP expression in vivo and in vitro, and MGP is necessary for VK1 to play a role in crystal deposition in cells. Conclusions: VK1 treatment can inhibit the formation of renal crystals in vivo. VK1 increases MGP expression and functions through MGP to reduce crystal deposition in cells and provide cell protection. Our findings suggest that VK1 treatment could be a potential strategy for the treatment and prevention of nephrolithiasis.